A virtual reality platform for the measurement of drinking topography. (1st February 2022) - Schneider, Victor J.; Bush, Nicholas; Vitus, Darya; Carpenter, Ryan W.; Robinson, Michael; Boissoneault, Jeff
Abstract: Background: The assessment of alcohol consumption during a drinking bout, known as drinking topography, may help improve understanding of biopsychosocial mechanisms underlying alcohol consumption. However, past studies have been limited by effort-intensive, time-consuming, and error-prone processes involved in collecting, organizing, and standardizing drinking topography data. Recent technologies allowing integrated data collection and greater environmental control, such as virtual reality (VR), could resolve these problems. Methods: In this pilot project, we assessed alcohol consumption topography of participants in a VR drinking environment with a programmable virtual confederate (i.e., bar goer) during two testing sessions. In one, the confederate drank quickly (30–60 s sip interval). In the other, the confederate drank slowly (60–120 s sip interval). Participants' hands and beverage were represented in VR. Between sips, beverages were placed on a Bluetooth-enabled scale, allowing real-time updates of drink weight. Participant experience was assessed after each testing visit. Multilevel modeling was used to characterize the effect of confederation condition on sip interval and sip volume. Descriptive analyses were used for participant experience data. Results: Results showed significant, moderate-to-strong between-visit correlations for topographic measures (r = 0.50 to r = 0.84) and indicate participants found the experience to be comfortable and acceptable. Multilevel models indicated participants had greater sip volumes and lower sip intervals when the confederate drank quickly. Conclusions: Future studies should take advantage of the considerable translational value of this technology to improve understanding of risk associated with individual drinking bouts and develop novel interventions for reducing hazardous drinking. Highlights: We developed a new VR platform to assess drinking topography. The INTACT VR platform is cost-effective and efficient to implement. Virtual confederate drinking rate significantly affected drinking topography. Participants found the VR experience comfortable and acceptable. Future studies should build towards assessments and interventions.